2017
DOI: 10.1097/fbp.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor and discriminative stimulus effects of four novel hallucinogens in rodents

Abstract: There has been increasing use of novel synthetic hallucinogenic compounds, 25B-NBOMe, 25C-NBOMe, 25I-NBOMe, and 5-MeO-DALT, which have been associated with severe toxicities. These four compounds were tested for discriminative stimulus effects similar to a prototypical hallucinogen (−)-2,5-dimethoxy-4-methylamphetamine (DOM) and to the entactogen (±)-3,4-methylenedioxymethamphetamine (MDMA). Locomotor activity in mice was tested to obtain dose range and time course information. 25B-NBOMe, 25C-NBOMe and 25I-NBO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…The serotonergic psychedelic effects of this compound have been confirmed by behavioral responses such as head twitch in C57BL/6J mice (NBOMe 0.1-1 mg/kg, s.c.) (Halberstadt and Geyer, 2014), wet dog shakes, and back muscle contraction (0.01-3 mg/kg, s.c.) in rats (Elmore et al, 2018), and all these effects were prevented by the administration of the selective 5-HT2A antagonist M100907 (Halberstadt and Geyer, 2014;Elmore et al, 2018). Indeed, 25I-NBOMe timedependently and dose-dependently decreased locomotor activity in mice (Eshleman et al, 2014;Gatch et al, 2017) and showed full substitution of LSD in rats drug discrimination and more than 50% of appropriate responding in MDMA-trained rats (Eshleman et al, 2014). The MDMA-like action of 25I-NBOMe has been also confirmed in vitro since it acts inhibiting the monoamine reuptake transporters with different IC 50 (hSERT, IC 50 = 4.3 µM; hDAT, IC 50 = 75 µM; hNET, IC 50 = 19 µM) in HEK 293 cells (Zwartsen et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…The serotonergic psychedelic effects of this compound have been confirmed by behavioral responses such as head twitch in C57BL/6J mice (NBOMe 0.1-1 mg/kg, s.c.) (Halberstadt and Geyer, 2014), wet dog shakes, and back muscle contraction (0.01-3 mg/kg, s.c.) in rats (Elmore et al, 2018), and all these effects were prevented by the administration of the selective 5-HT2A antagonist M100907 (Halberstadt and Geyer, 2014;Elmore et al, 2018). Indeed, 25I-NBOMe timedependently and dose-dependently decreased locomotor activity in mice (Eshleman et al, 2014;Gatch et al, 2017) and showed full substitution of LSD in rats drug discrimination and more than 50% of appropriate responding in MDMA-trained rats (Eshleman et al, 2014). The MDMA-like action of 25I-NBOMe has been also confirmed in vitro since it acts inhibiting the monoamine reuptake transporters with different IC 50 (hSERT, IC 50 = 4.3 µM; hDAT, IC 50 = 75 µM; hNET, IC 50 = 19 µM) in HEK 293 cells (Zwartsen et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…There are several case reports of abuse of 25BNBOMe, 25C-NBOMe, and 25I-NBOMe and their harmful effects include prolonged agitation, hallucinations, seizures, rhabdomyolysis, acute kidney injury and death [610]. In animal studies, these three NBOMe compounds substituted for the discriminative stimulus effects of the hallucinogen DOM [11] and were recently categorized as Schedule 1 compounds [12]. There is much less information available regarding other NBOMe compounds although anectodal evidence indicates that many are psychoactive and hallucinogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ketanserin, a 5-HT 2A antagonist, blocked the 25B-NBOMe-evoked HTR and normalized 5-HT 2A mRNA levels in the mouse prefrontal cortex upregulated by a prolonged administration of the drug (Custodio et al, 2019). Gatch et al (2017) tested 25B-NBOMe, 25C-NBOMe, and 25I-NBOMe for discriminative stimulus effects similar to a prototypical psychedelic/hallucinogen DOM and to an empathogen, 3,4-methylenedioxymethamphetamine (MDMA). In DOM-trained rats 25B-NBOMe and 25C-NBOMe, but not 25I-NBOMe, fully substituted for this drug.…”
Section: Pharmacology Of Nbomesmentioning
confidence: 99%
“…In both tests, the dose-effect curves for 25B-NBOMe had an inverted U-shape. It is suggested that 25B-NBOMe and 25C-NBOMe are most likely used as recreational psychedelics, although 25B-NBOMe may also be used as an empathogenic compound (Gatch et al, 2017). However, the latter assumption should be taken with caution, as some compounds (e.g., fenfluramine) that substitute for MDMA in rats do not produce MDMA-like empathogenic effects in humans (Schechter, 1988).…”
Section: Pharmacology Of Nbomesmentioning
confidence: 99%